Fracture reorientation mechanism during hydraulic fracturing based on XFEM simulation - Li, Xiaolong (Frontiers in Earth Science, 2024)
Understanding the reorientation mechanism of near-wellbore hydraulic fractures is very important for optimizing parameters in field fracturing treatments. In this study, a fully 2D coupled seepage–stress model based on the extended finite element method (XFEM) model is applied to investigate the fracture trajectory and reorientation. The numerical model considering pore pressure is verified by a true triaxial laboratory experiment. The results show that the fracture is generally initiated from perforation and rotates to the direction of maximum horizontal stress with different curving distances. The fracture trajectory and reorientation distance can be influenced by the rock mechanics and fracturing application parameters, including elasticity modulus, Poisson’s ratio, tensile strength, perforation angle, horizontal stress difference, and injection rate. More exact behavior of fracture propagation can be described according to the parametric study. The results provided in this paper can be clearer in the prediction of the fracture trajectory and fracturing design in the near-wellbore region.